Preservation of Local Wisdom Values of Sipakatau, Sipakalebbi, Sipakainge in Curriculum Development at PTKIN - HR, Sabriadi; Wakia, Nurul (LPPM Universitas Ibn Khaldun, Bogor, 2025)
This research aims to explore the application of the local wisdom of sipakatau, sipakalebbi, sipakainge into the curriculum at PTKIN. The focus of this research is the weak design of local wisdom implemented in formal curriculum documents. The author used a qualitative approach with explorative case study as the research design. In-depth interviews, participatory observation and document analysis were the data collection techniques used and analyzed using the Miles and Huberman model. The results showed that the value of local wisdom has existed in campus social interactions, but has not been formally outlined in the curriculum. The results of the analysis reveal that there are major challenges, namely a lack of balance with institutional awareness and the assumption that local values are the antithesis of the demands of globalization. On the other hand, there are great opportunities through intersectoral cooperation, strengthening the competence of lecturers and reforming curriculum documents based on local wisdom. This research introduces a three-stage implementation model, namely: alignment of the vision and mission of the institution, formulation of learning outcomes based on local wisdom values, and lecturer training.